The transcription of identities : a study of V.S. Naipaul's postcolonial writings - Zhou, Min (Cultural studies (Transcript (Firm)) ;, 2015)
Based on a study of V.S. Naipaul's postcolonial writings, this book explores the process of postcolonial subjects' special route of identification. This enables the readers to see how in our increasingly diverse and fragmented post-modern world, identity is a vibrant, complex, and highly controversial concept. The old notion of identity as a prescribed and self-sufficient entity is now replaced by identity as a plural, floating and becoming process. Min Zhou shows how postcolonial literature, among other artistic forms, is one of the most representative reflections of this floating identity.